henn-1/HEN1 Promotes Germline Immortality in Caenorhabditis elegans - Svendsen, Joshua M. (Cell Rep, 2019)
The germline contains an immortal cell lineage that ensures the faithful transmission of genetic and, in some instances, epigenetic information from one generation to the next. Here, we show that in Caenorhabditis elegans, the small RNA 3′-2′-O-methyltransferase henn-1/HEN1 is required for sustained fertility across generations. In the absence of henn-1, animals become progressively less fertile, becoming sterile after ~30 generations at 25°C. Sterility in henn-1 mutants is accompanied by severe defects in germline proliferation and maintenance. The requirement for henn-1 in transgenerational fertility is likely due to its role in methylating and, thereby, stabilizing Piwi-interacting RNAs (piRNAs). However, despite being essential for piRNA stability in embryos, henn-1 is not required for piRNA stability in adults. Thus, we propose that methylation is important for the role of piRNAs in establishing proper gene silencing during early stages of development but is dispensable for their role in the proliferated germline.